Model rachunku kosztów działań dla działalności dydaktycznej w Szkole Głównej Handlowej. Wyniki badań przedwdrożeniowych - Świderska, Gertruda; Podłowski, Piotr; Rybarczyk, Krzysztof; Borowski, Szczepan; Kariozen, Michał (An Activity-based Costing Model For Educational Activities at the Warsaw School of Economics, 2005)
The purpose of the study was to prepare an activity-based costing (ABC) model for the Warsaw School of Economics (WSE), which would allow to overcome management information gaps. The study was conducted from 2002 to 2004 and consisted of six phases: 1) analyzing the current state of cost information at WSE, 2) specifying information needs at WSE, 3) constructing a framework for an ABC model at WSE, 4) building of the model for educational activities at WSE, 5) implementing the model using OROS Lite Modeler, and 6). establishing procedures for data collection. The paper presents results of the studies for each phase of the project.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 326-336